MAKNA LAKON SRI MULIH DALAM PERTUNJUKAN WAYANG RELEVANSINYA DENGAN KETAHANAN PANGAN - Sunardi, Sunardi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This paper aims to examine the meaning of wayang performances in relation to people’s lives. Sri Mulih’s play in a wayang performance as a representation of Indonesia’s food security. The Sri Mulih story reveals the character of Dewi Sri, who is believed by the community to symbolize the goddess of rice, food, or prosperity. Sri Mulih’s story is an artistic expression that grew out of the culture of an agrarian society to reinforce hopes for food security so that a fertile and prosperous life can be realized. The problem discussed is why the Sri Mulih story represents food security. To study this problem, the hermeneutic theory is used to seek and find the meaning contained in the object of study in the form of phenomena of human life, through understanding and interpretation. The research method uses literature and observation. Literature study by tracing various literary sources and studies on the story of Sri Mulih. Observations were made by observing the wayang performances story abaut Sri Mulih. The results of the study show that: first, the myth of Dewi Sri is interpreted as a symbol of fertility for agricultural land in agrarian communities; secondly, the essence of the Sri Mulih story is the disappearance of catastrophes in various countries because of the presence of Dewi Sri and Batara Sadana; and third, the teachings of the Sri Mulih story have a meaning about food security for Indonesian people. The conclusion of this paper states that the Sri Mulih story as an original Indonesian cultural product is used as a vehicle for the expression of an agrarian society to realize hopes regarding people’s prosperity so that food security is realized.